Dissection of heterocellular cross-talk in vascularized cardiac tissue mimetics. (January 2020) - Wagner, Julian Uwe Gabriel; Pham, Minh Duc; Nicin, Luka; Hammer, Marie; Bottermann, Katharina; Yuan, Ting; Sharma, Rahul; John, David; Muhly-Reinholz, Marion; Tombor, Lukas; Hardt, Martin; Madl, Josef; et al.
Abstract: Cellular specialization and interaction with other cell types in cardiac tissue is essential for the coordinated function of cell populations in the heart. The complex interplay between cardiomyocytes, endothelial cells and fibroblasts is necessary for adaptation but can also lead to pathophysiological remodeling. To understand this complex interplay, we developed 3D vascularized cardiac tissue mimetics (CTM) to study heterocellular cross-talk in hypertrophic, hypoxic and fibrogenic environments. This 3D platform responds to physiologic and pathologic stressors and mimics the microenvironment of diseased tissue. In combination with endothelial cell fluorescence reporters, these cardiac tissue mimetics can be used to precisely visualize and quantify cellular and functional responses upon stress stimulation. Utilizing this platform, we demonstrate that stimulation of α/β-adrenergic receptors with phenylephrine (PE) promotes cardiomyocyte hypertrophy, metabolic maturation and vascularization of CTMs. Increased vascularization was promoted by conditioned medium of PE-stimulated cardiomyocytes and blocked by inhibiting VEGF or upon β-adrenergic receptor antagonist treatment, demonstrating cardiomyocyte-endothelial cross-talk. Pathophysiological stressors such as severe hypoxia reduced angiogenic sprouting and increased cell death, while TGF β2 stimulation increased collagen deposition concomitant to endothelial-to-mesenchymal transition. In sum, we have developed a cardiac 3D culture system that reflects native cardiac tissue function, metabolism and morphology - and for the first time enables the tracking and analysis of cardiac vascularization dynamics in physiology and pathology. Graphical abstract: Unlabelled Image Highlights: Vascularized cardiac tissue mimetics serve as a model to study intercellular tissue cross-talk and transdifferentiation Adrenergic receptor stimulation with phenylephrine increased maturation and vascularization of cardiac tissue mimetics Induction of vascularization by adrenergic receptor stimulation occurs through cardiomyocyte-endothelial cross-talk